Productivity of different species of sainfoin depending on the elements of cultivation technology - Г. І. Демидась; Е. С. Лихошерст; Л. М. Бурко; К. Ф. Гузь (Plant Varieties Studying and Protection)
Purpose. To determine the features of the leaf surface area formation and the dynamics of growth of the vegetative mass of various sainfoin species depending on the influence of mineral fertilizers and inoculation. Methods. Field, laboratory, statistical. Results. In the course of experimental studies, the morphological features of plants in the process of growth and development of various sainfoin species were studied. As our studies showed, all sainfoin species had different plant densities, which accordingly affected the leaf surface area. In the budding phase, the leaf surface area of plants of the first year in continuous cultivation ranged from 17.01 to 24.3 thousand m2/ha on average over three years; in particular, from 18.06 to 24.3 – for common sainfoin; 17.6–20.5 – for transcaucasus sainfoin and 17.1–20.3 thousand m2/ha – for sand sainfoin. The maximum leaf surface area of the plants of the first year of cultivation, regardless of its species, was observed during flowering with the application of complete mineral fertilizer (N45P60K90). In areas without fertilizer this figure was much lower. In the experiments, an increase in the leaf surface on all three studied species and sainfoin varieties from the first to the third year of their cultivation was clearly observed. According to the results of gross productivity for 2 mowings, it was found that common sainfoin forms the maximum increase of top with complete mineral fertilizer and seed inoculation – 43.03 t/ha. Conclusions. The productivity of sainfoin crops depended mostly on the application of complete fertilizer at a dose of N45P60K90 + inoculation of seeds. To a much lesser extent, the species of sainfoin and the cutting height of the first mowing of the grass stand affected its productivity. It was revealed that the greatest dynamics of vegetative mass growth was observed in common sainfoin, and the smallest was recorded in sand sainfoin.